Re-Examining Richard Bauckham’s Argument from Name Popularity in Light of Apocryphal and Talmudic Evidence - Gregor, Kamil (Journal for the study of the New Testament, 2024)
This article re-examines the argument from name popularity appearing in the ‘Palestinian Jewish Names’ chapter of Richard Bauckham’s Jesus and the Eyewitnesses in light of patterns of the name popularity found in extra-biblical texts. Bauckham postulates that if Gospels-Acts contained named characters invented in the process of anonymous community transmission, the statistical distribution of name popularity in Gospels-Acts would not align well with the distribution in the ancient Palestinian Jewish population, particularly if the invention took place in the Diaspora. We test this by analyzing the name popularity in two corpora of texts that contain many recognizably fictitious first-century Palestinian Jewish characters, namely a corpus of Christian extra-biblical works consisting of the Clementine Homilies, the Acts of Pilate, and Solomon of Bosra’s Book of the Bee, and the corpus of the Babylonian Talmud. Contra Bauckham, name popularity distributions in these two corpora do not correspond to the distribution among first-century Palestinian Jews statistically significantly worse than the distribution in Gospels-Acts. Moreover, the two corpora paradoxically align better in some respects because they do not exhibit a disproportional representation of specific names observed in Gospels-Acts.